ANALISIS PELAKSANAAN PROGRAM PENGENDALIAN PENYAKIT TIDAK MENULAR DI POSBINDU PTM PUSKESMAS ROKAN IV KOTO I KABUPATEN ROKAN HULU : Analisis Pelaksanaan Program Pengendalian Penyakit tidak Menular di Posbindu PTM Puskesmas Rokan IV Koto I Kabupaten Rokan Hulu - Kholida Hosni; Dedi Afandi; Jasrida Yunita; Doni Jepisah; Ahmad Hanafi (STIKes Hang Tuah Pekanbaru, 2020)
The implementation of the Non-Communicable Disease Control Program carried out in Posbindu PTM is a concrete manifestation of community participation in implementing early detection, monitoring and early follow-up of Non-Communicable Disease risk factors independently and continuously. Rokan IV Koto I Community Health Center has implemented PTM control in an integrated manner but the scope of Non-Communicable Disease prevention and eradication efforts is still low at 53,9%. The purpose of the study was to determine the implementation of the control program for non-communicable diseases in Posbindu PTM Rokan IV Koto I Community Health Center seen from input indicators and processes of the Non-Communicable Disease Control Program. This type of research is qualitative. 8 informants consisted of midwives midwives in charge of posbindu, mobilizing midwives, monitoring midwives, counselor doctors, recording cadres, Head of Sub-Division of Administration, community leaders, BPJS. The tringulation used is source tringulation, methods and data. The results of the study show that inputs (human resources, incentives, facilities and facilities) have been done well even though the use of Posbindu PTM facilities and equipment is not yet available in every village. The process (identification of potential PTM problems, implementation of activities and program innovations, recording and reporting, early risk follow-up and referral of PTM) has gone well. BASMI PELAKOR 1 innovation was able to increase the coverage of community visits to Posbindu PTM to 57,4% which previously had been in 2018 at 53,92%. Suggestion for Community Health Center to facilitate the formation of partnerships in each village through CSR (Corporate Social Responsibility) to buy their own tools, deliberation with the community to determine the Posbindu PTM schedule that is mutually agreed upon, involve community participation in implementing BASMI PELAKOR. Keywords : Implementaon of PTM Control Program, Input of PTM program implementaon. PTM program implementaon process.